Optimizing the process of verifying counterparties in the banking sector: connecting sanction sites under a single interface - Akhmedova, Iroda; Tursunov, Nodirkhuja (MMIT Proceedings, 2024)
The project work is devoted to the development of a software solution "Sanctions Compliance", designed to conduct a comprehensive check of sanctions risks of counterparties and goods. In today's banking sector, the effective implementation of sanctions checks plays a key role in meeting regulatory requirements and preventing financial risks. The offered software simplifies and speeds up the process of verifying clients and transactions, providing a single interface for accessing sanctions sites.